Wind-resistance and seismic behavior of a steel frame elevator with square hollow section members and semi-rigid joints - Zhao, Bi-Da; Xu, Chao-Chao; Zhu, Hao-Chuan; Chen, Rui-Sheng; Wu, Jia-Li; Qi, Yuan-Sen; Jin, Zhen-Fen (Frontiers in Built Environment, 2024)
This article presents a study of the wind-resistance and seismic behavior of steel frame elevator structures with square hollow section (SHS) members. The study was conducted by numerical analysis, it begins by examining the semi-rigid performance of SHS T-joints (beam-column joints) under in-plane bending moment, proposes a semi-rigid connection model for the joints, and then investigates the influence of semi-rigid joint effect on the performance of the steel elevators. Finite element (FE) results showed that the semi-rigid model can predict the moment-rotation response of the beam-column joints. The results also showed that the natural vibration period of the elevator with semi-rigid joints is 20% higher than that of an elevator with rigid joints. The semi-rigid joint effect causes the lateral drift of the elevator to increase by more than 47% under wind load, causing the maximum story drift of the elevator to exceed the limit specified in the current code. The semi-rigid joint effect causes the lateral displacement of the elevator to increase by approximately 15%–30% under the seismic waves of a rare earthquake.